2018
DOI: 10.1108/compel-04-2017-0170
|View full text |Cite
|
Sign up to set email alerts
|

Topology optimization in electromagnetism using SIMP method

Abstract: Purpose In this work, the authors deal with topology optimization in electromagnetism using solid isotropic material with penalization (SIMP) method associated with a gradient-based algorithm. The purpose of this study is to propose and investigate the impact of new generalized material interpolation scheme (MIS) used in SIMP approaches. Design/methodology/approach The variable domains of this kind of electromagnetism design problem are decomposed into small squares which represent a material point (iron her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…This method was introduced by Bendsøe et al in Sigmund, 2003, 1999) and it is based on the homogenization theory method. Moreover, a SIMP method is used here, because it owns some efficiency to solve our applications (Sanogo et al, 2014;Sanogo, 2016;Sanogo and Messine, 2016;Sanogo and Messine, 2018).…”
Section: Solid Isotropic Materials With Penalization Methods Penalization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method was introduced by Bendsøe et al in Sigmund, 2003, 1999) and it is based on the homogenization theory method. Moreover, a SIMP method is used here, because it owns some efficiency to solve our applications (Sanogo et al, 2014;Sanogo, 2016;Sanogo and Messine, 2016;Sanogo and Messine, 2018).…”
Section: Solid Isotropic Materials With Penalization Methods Penalization Methodsmentioning
confidence: 99%
“…Thus, the fact that arctan is a non-convex function is not relevant. However, there are other convex penalization functions that was used and tested in (Bendsøe and Sigmund, 2003;Sanogo et al, 2014;Sanogo, 2016;Sanogo and Messine, 2018;Luk aš and Chalmovianský, 2007). But the numerical tests showed that the choice of a convex penalization function appears to be not necessary.…”
Section: Solid Isotropic Materials With Penalization Methods Penalization Methodsmentioning
confidence: 99%
“…However, it presents some symmetry issues and favors low ρ associated material in the final design. In [31], the authors compared this scheme to other schemes and concluded that the final design was not as good as many other proposed ones. To solve symmetry issues introduced by the classical polynomial interpolation, D. Lukàš introduced a new scheme in [21]:…”
Section: Materials Interpolation Schemesmentioning
confidence: 99%
“…Indeed, gray materials do not necessarily have a proper physical interpretation or may represent, in the best case, a microstructure that is complex to manufacture [8]. A common solution for removing gray materials proposed by the literature involves penalizing the material interpolation, such as the Solid Isotropic Materials with Penalization (SIMP) scheme [8,9]. Yet topology optimization problems are generally ill-posed, and other numerical artifacts can occur, such as checkerboards that need regularization (e.g., numerical filtering [10]).…”
Section: Introductionmentioning
confidence: 99%